Sport as a Common Property Resource: A Solution to the Dilemmas of Doping - Edward J. Bird; Gert G. Wagner (Journal of Conflict Resolution, 1997)
The use of drugs in high-performance sports (doping) is a common pool resource (CPR) dilemma: regardless of the number of other athletes who dope, the athlete with strong tastes for victory will find doping optimal; yet if all athletes dope, they all bear negative health consequences, although each one's odds of victory are not greatly changed. The current regulatory approach relies entirely on centralized bureaucratic methods and is ineffective. The authors use insights developed in the common property resource literature and the theory of social norms to analyze the failure of these methods. The programs they propose—the drug diary and a collegial enforcement system—are superior to the current system in that they encourage the development of athletic norms against unfair drug use. In the end, such norms are the only hope for controlling doping, which is becoming increasingly difficult to observe. Empirical evidence shows that such norms against unobservable sports violations can be very powerful. Norms of conduct in golf, for example, successfully enforce that sport's many rules regulating unobservable aspects of play.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively
Keywords: 330; Doping; Sport